Copper‐Catalyzed Regioselective Intramolecular Oxidative α‐Functionalization of Tertiary Amines: An Efficient Synthesis of Dihydro‐1, 3‐Oxazines1. Issue 37 (24th July 2013) - Deb, Mohit L.; Dey, Suvendu S.; Bento, Isabel; Barros, M. Teresa; Maycock, Christopher D.
<x xml:space="preserve">Abstract</x> Traffic control: The hydroxy functional group directs the α‐functionalization of tertiary amines, synthesizing 1, 3‐oxazines by CO bond formation. Reaction occurs with both benzylic and non‐benzylic amines. In the case of naphthoxazine synthesis, 100 % diastereoselectivity was observed. A tentative two‐pathway mechanism is proposed for the reaction.<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>